2023
DOI: 10.3390/biomedicines11030731
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study on the Role of Metformin in Colorectal Cancer Liver Metastases

Abstract: Colorectal cancer liver metastases (CRCLMs) have two main histopathological growth patterns (HPGs): desmoplastic (DHGP) and replacement (RHGP). The vascularization in DHGP tumours is angiogenic, while the RHGP tumours exert vessel co-option vasculature. The presence of vessel co-option tumours is associated with poor response to anti-angiogenic agents and chemotherapy, as well as a worse prognosis. Metformin has been shown to influence the progression and vasculature of tumours in different cancers. However, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Therefore, the tumours that utilize vessel co-option vascularization are resistant to anti-angiogenic therapy (7). Vessel co-option is a predominant vascularization in CRCLM (7,9). We previously reported that CRCLM patients with predominantly angiogenic metastasis receiving neoadjuvant antiangiogenic plus chemotherapy have significantly higher 5-year overall survival compared to the patients with co-opting tumours who have received the same treatment (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the tumours that utilize vessel co-option vascularization are resistant to anti-angiogenic therapy (7). Vessel co-option is a predominant vascularization in CRCLM (7,9). We previously reported that CRCLM patients with predominantly angiogenic metastasis receiving neoadjuvant antiangiogenic plus chemotherapy have significantly higher 5-year overall survival compared to the patients with co-opting tumours who have received the same treatment (7).…”
Section: Discussionmentioning
confidence: 99%
“…The fundamental histopathological feature of DHGP lesions is the presence of a desmoplastic rim at the tumour periphery that separates cancer cells from liver parenchyma (7). However, the desmoplastic rim is absent in RHGP lesions, and the cancer cells infiltrate through adjacent liver plates (9,10). Moreover, angiogenesis is the predominant vascularization in DHGP tumours (7).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some scholars have begun to study the effect of metformin on VC of liver cancer in recent years. A study showed that CRCLM patients treated with metformin have fewer co-option vessels than unused patients (99). At the same time, Li et al have shown that metformin can improve the chemotherapy resistance of non-angiogenic colorectal cancer by increasing microvessel density and restoring vascular function and maturity (100).…”
Section: Other Treatmentsmentioning
confidence: 99%
“…Also, the Rada et al study in 108 liver mCRC patients has shown a decrease in mortality rates and better prognosis in the metformin group than in non-diabetic and other anti-diabetic medication users. They related such metformin benefits to the ability of metformin to decrease co-option vasculature in liver metastasis, a strong indicative of poor prognosis[34]. On the contrary, the observational study by Cossor et al analyzed 2066 post-menopausal diabetic CRC women for a median follow-up period of 4.1 years and showed no significant difference in CRC-specific survival in the metformin group in comparison to non-diabetics and other oral anti-diabetic medication groups[35].…”
mentioning
confidence: 99%